The Role of External Auditors in Improving Cybersecurity Audits in Financial Reporting: A Case Study at PT Pelayaran Logistik Indonesia - Evi Julyanti Situmorang (Journal of Accounting and Finance Management, 2026)
This study explores the role of external auditors in conducting cybersecurity audits and their contribution to improving the quality of financial reporting. Using a qualitative case study approach at PT Pelayaran Logistik Indonesia, a logistics company in Indonesia, data were collected through semi-structured interviews with seven key informants, including external auditors, financial managers, and information technology personnel. Thematic analysis, following Braun and Clarke’s framework, identified three main themes: the strategic role of external auditors in cybersecurity evaluation, the multidimensional challenges of conducting cybersecurity audits, and the effectiveness of cybersecurity audits in enhancing financial statement quality. The findings reveal that external auditors play a critical role in assessing digital security controls, identifying system vulnerabilities, and providing recommendations for technology-based improvements to internal controls. However, auditors face significant challenges, including limited technical competence, restricted access to internal systems, and the absence of explicit regulatory frameworks governing cybersecurity integration in financial audits. Despite these challenges, cybersecurity audits positively impact financial reporting by improving digital documentation, strengthening access controls, and enhancing transparency. This study contributes to the auditing literature by demonstrating the need for cross-disciplinary competence and collaborative audit approaches in the digital era.